The Impact of Emotional Intelligence, Professionalism, and Compensation on Work Productivity: Study at A Manufacturing Company in Pasuruan - Ayu Nanda Setyaningrum; Vivin Maharani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study aims to explore the effects of emotional intelligence and professionalism on employee productivity at a manufacturing company in Pasuruan, while also assessing the role of compensation in enhancing productivity. It examines how emotional intelligence, professionalism, and compensation concurrently influence employee productivity. The research population comprises all employees working at the company, totaling 85 individuals. A saturation sampling method is employed, resulting in a sample size of 85 respondents. The study utilizes a quantitative descriptive methodology for data collection and analysis. The findings reveal that emotional intelligence, professionalism, and compensation each have a positive and significant impact on employee productivity. Moreover, these three variables collectively contribute to enhancing work productivity among employees. The implications of this research are significant for management and human resource practices. Understanding that emotional intelligence plays a crucial role highlights the need for organizations to promote emotional skills among employees. This could be achieved through training programs that enhance emotional competencies, enabling employees to work better in teams, handle stress effectively, and improve their interactions with colleagues and clients. Additionally, the positive influence of professionalism emphasizes the importance of fostering a professional work culture within the organization. Management should focus on creating an environment that values accountability, ethical behavior, and continuous improvement. Furthermore, the significant effect of compensation reinforces the necessity for competitive remuneration packages that recognize and reward employee contributions. By addressing these aspects—emotional intelligence, professionalism, and compensation—organizations can create a more motivated workforce that drives higher productivity and achieves company goals. Overall, these findings provide valuable insights for enhancing human resource strategies and improving overall organizational performance in the competitive manufacturing sector.